(untitled) (Research, Society and Development, 2023)
Objective: SARS-CoV-2, Influenza A (IAV) and Influenza B (IBV) epidemiological investigation in the community served by the MonitoraCOVID program of the Federal University of Minas Gerais (UFMG) in 2022 through the standardization and validation of the LAMP technique. Method: Nasopharyngeal swab samples were used in the LAMP reactions, performed simultaneously under the same conditions with visual reading. For epidemiological investigation, 10% of the monthly amount assisted by MonitoraCOVID were tested. Results: LAMP reactions demonstrated sensitivity of 84.0% and 85.2% for SARS-CoV-2 and IAV respectively. The prevalence of IBV was low for analysis of analytical parameters. The specificity obtained was 100% in the three reactions. The annual positivity rate found was: SARS-CoV-2 - 28.7%, IAV - 1.6%, IBV - 0.0%. Indeterminate results were found for SARS-CoV-2 and IAV (0.8% each). Conclusion: The LAMP assay was able to assess the epidemiology of respiratory viruses, and it could be applied in the diagnosis in other populations.